Application of fuzzy analytic hierarchy process for development of risk index for elevated corridor metro rail project in Western India. (2017) - Sarkar, Debasis; Singh, Manvinder; Raghavendra, H.B.
Construction of elevated corridor metro rail projects involves activities like piling works, pier construction, segment casting, segment transportation, segment erection with launching girder and pre-stressing operations for joining the segments which are risky in nature and need to be implemented very carefully. This paper is an attempt to develop a risk index for the elevated corridor for metro rail construction project in western India. The risk index is developed by application of fuzzy analytic hierarchy process (FAHP) to the quality parameters associated with the piling works, pier construction, segment casting, transportation and erection. This risk index would help the project authorities to identify the most risky activities and plan accordingly the suitable risk mitigation measures. This would help the project to be completed successfully within stipulated time and cost frame. The risk index developed would act as a guide for developing risk management strategies for the future metro rail construction projects.